2011
DOI: 10.1055/s-0030-1271050
|View full text |Cite
|
Sign up to set email alerts
|

Die Ellenbogentotalendoprothese in der Versorgung schwerer Ellenbogenverletzungen des älteren Patienten

Abstract: Due to the good functional outcome and pain relief of patients treated by total elbow replacement, we suggest that total elbow arthroplasty is a reasonable treatment option for complex acute and chronic injuries of the elbow in elderly patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 9 publications
0
10
0
2
Order By: Relevance
“…In a similar study in Turkey, 72% of parents were informed about the safety seats [18]. Moreover, the source of advice in our research was mostly from relatives and lay people, and then from the media, and only 4% reported receiving advice from physicians.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…In a similar study in Turkey, 72% of parents were informed about the safety seats [18]. Moreover, the source of advice in our research was mostly from relatives and lay people, and then from the media, and only 4% reported receiving advice from physicians.…”
Section: Discussionmentioning
confidence: 85%
“…Other reports from Turkey and the US have also shown parents of higher socio-economic class to have higher WTP [18,8]. Using a contingent valuation questionnaire, Mataria et al, have also demonstrated that WTP for "luxury" quality attributes is negatively affected by both income-dependent and income-independent impoverishment [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…80 % und nach 20 Jahren ca. 60 % der Prothesen ohne Anzeichen eines Implantatversagens oder einer Prothesenlockerung [2,4,6,11,12,[16][17][18].…”
Section: Ergebnisse Nach Gelenkersatzunclassified